Hobbes, Locke, and confusion's masterpiece : an examination of seventeenth-century political philosophy - Harrison, Ross (Cambridge University Press, 2003)
In this major study of the foundations of modern political theory the eminent political philosopher Ross Harrison explains, analyzes, and criticizes the work of Hobbes, Locke, and their contemporaries. He provides a full account of the turbulent historical background that shaped the political, intellectual, and religious content of this philosophy.